2022
DOI: 10.1016/s1470-2045(21)00589-1
|View full text |Cite
|
Sign up to set email alerts
|

Residual cancer burden after neoadjuvant chemotherapy and long-term survival outcomes in breast cancer: a multicentre pooled analysis of 5161 patients

Abstract: Background Previous studies have independently validated the prognostic relevance of residual cancer burden (RCB) after neoadjuvant chemotherapy. We used results from several independent cohorts in a pooled patient-level analysis to evaluate the relationship of RCB with long-term prognosis across different phenotypic subtypes of breast cancer, to assess generalisability in a broad range of practice settings. MethodsIn this pooled analysis, 12 institutes and trials in Europe and the USA were identified by perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
110
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 244 publications
(119 citation statements)
references
References 32 publications
(68 reference statements)
7
110
2
Order By: Relevance
“…At the time of surgery (approximately 6 months following core biopsy collection and after all qSMLM data were computed), clinical outcomes and residual cancer burden (RCB) indices were noted. The RCB index (RCB-0 to RCB-III) was designed to quantify residual disease in the tumor bed and lymph nodes after neoadjuvant therapy; it is a well validated prognostic indicator for breast cancer [ 112 , 113 ]. Our sample cohort comprised the following: P18 had RCB-I, P20 had RCB-II, and all other women had achieved a pathological complete response (pCR) equivalent to RCB-0.…”
Section: Resultsmentioning
confidence: 99%
“…At the time of surgery (approximately 6 months following core biopsy collection and after all qSMLM data were computed), clinical outcomes and residual cancer burden (RCB) indices were noted. The RCB index (RCB-0 to RCB-III) was designed to quantify residual disease in the tumor bed and lymph nodes after neoadjuvant therapy; it is a well validated prognostic indicator for breast cancer [ 112 , 113 ]. Our sample cohort comprised the following: P18 had RCB-I, P20 had RCB-II, and all other women had achieved a pathological complete response (pCR) equivalent to RCB-0.…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been recognized that the binary approach of pCR and non-pCR does not stratify the risk groups optimally. Yau et al introduced a categorization according to the residual disease burden, which categorizes the tumor into three grades, according to the size of the residual tumor [ 32 ]. The authors recently found that with an increase in the residual cancer burden, the outcome worsened.…”
Section: Future Approachesmentioning
confidence: 99%
“…Neoadjuvant chemotherapy (NAC), is currently used for the treatment of aggressive breast carcinomas that are nonetheless operable [ 6 ], to increase conservative breast surgery rates [ 7 ]. Neoadjuvant chemotherapy has many advantages such as a less extensive breast and axillary surgery and a monitoring of the treatment response [ 8 , 9 ]. Pathological complete response (pCR) has been reported to occur in about 20–60% of patients on NAC, and is associated with better survival outcomes [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%